The official Peruvian position regarding maritime areas of UnClos from the maritime dispute with Chile - Namihas, Sandra (2014)
The article purports to express how, in the course of and subsequent to the proceedings in The Hague, the Peruvian Government has defined the legal nature of its 200 miles of maritime domain, by assuming its compatibility with the maritime zones established by United Nations Convention on the Law of the Sea (UnClos).